Pelatihan EViews untuk Meningkatkan Kualitas Analisis Data Skripsi Mahasiswa JPP FT UNM: id - Wardimansyah Ridwan; Fitry Purnamasari; Andi Khaerun Niza; Ayu Saputri Bahar; Syamsuriah (V-MACHINE: Vocational and Mechanical Community Service Journal, 2026)
Data analysis skills are an essential part of thesis writing, especially for students who use quantitative research approaches. However, many students still face difficulties in preparing data, selecting appropriate analytical techniques, reading statistical outputs, and presenting the results in academic writing. This community service activity aimed to improve students’ ability to analyze thesis data through EViews training. The activity was attended by 50 sixth-semester students of the Department of Tourism and Hospitality, Faculty of Engineering, Universitas Negeri Makassar, and was conducted in one of the classrooms at the Faculty of Engineering on Saturday, April 11, 2026. The training methods included short lectures, demonstrations, hands-on practice, discussions, and assistance in interpreting EViews outputs. The training materials covered an introduction to EViews, data input, regression analysis, output reading, and the preparation of interpretations of the analysis results. The activity showed that students gained a better understanding of the stages of data analysis and practical experience in using EViews to support thesis writing. This training can serve as an academic assistance model to strengthen students’ readiness in conducting data analysis for their theses